Augmentation in restless legs syndrome: an eye tracking study on emotion processing. Issue 9 (12th August 2020) - Ellmerer, Philipp; Heim, Beatrice; Stefani, Ambra; Peball, Marina; Werkmann, Mario; Holzknecht, Evi; Bergmann, Melanie; Brandauer, Elisabeth; Sojer, Martin; Zamarian, Laura; Delazer, Margarete; Seppi, Klaus; et al.
Abstract: Objective: To assess emotional processing and alexithymia in patients with restless legs syndrome (RLS) with augmentation versus those who never had augmentation. Methods: We recruited 26 patients who had a history of augmentation (AUG), either current or past, 27 RLS patients treated with dopamine agonists who never had augmentation (RLS controls), and 21 healthy controls (HC). All participants were screened for impulse control disorders (ICDs). Alexithymia was assessed by means of the Toronto Alexithymia Scale – 20 (TAS‐20). Facial emotion recognition was tested through an eye‐tracking task. Furthermore, all participants performed neuropsychological tests assessing global cognitive status, impulsivity, anxiety, and depression. Results: ICD symptoms occurred more frequently in AUG patients than in RLS controls ( P = 0.047). Patients with AUG scored higher on the TAS‐20 ( P = 0.007) and the attentional subdomain of an impulsivity scale (BIS‐11; P = 0.015) compared to HC. Patients with AUG also performed worse on the facial emotion recognition task relative to RLS controls ( P = 0.009) and HC ( P = 0.003). We found a group difference for the time to first fixation and the fixation count in the mouth region ( P = 0.019 and P = 0.021, respectively). There were no other differences in the eye tracking examination. Interpretation: This study showed evidence of poorer emotional processing in patients who had augmentation compared to RLS patients without augmentation and healthy controls. The altered exploration pattern of faces and the higher alexithymia scores suggest abnormalities in emotion processing in patients with augmentation.